Effect of Season on Arabian Camel (Camel us Dromedarius) Semen Parameters - Hayder A.N. AL-Zamely (Journal of Global Pharma Technology, 2018)
This study was conducted on forty (40) of one- hamped Arabin camels to evaluate the effect of season on semen parameters, therefore the semen was collected from these animals in four seasons which are Winter, Autumn, Spring and Summer, the parameters which are studied include: semen concentration, semen motility, semen volume, the percentage of life sperms and the percentage of abnormal sperms. The results were revealed that, there is significant increase in sperms concentration, semen volume and semen motility during cold seasons (Winter and Autumn) as compared with other seasons also there is increase in percentage of life sperms and decrease in percentage of abnormal sperms in cold seasons (Winter and Autumn) as compared with other seasonsKeywords: Arabian camel, semen, season.